A Cross-Sectional and Longitudinal Study to Define Alarmins and A-SAA Variants as Companion Markers in Early Rheumatoid Arthritis - Ciregia, Federica; Nys, Gwenaël; Cobraiville, Gaël; Badot, Valérie; Di Romana, Silvana; Sidiras, Paschalis; Sokolova, Tatiana; Durez, Patrick; Fillet, Marianne; Malaise, Michel G.; de Seny, Dominique (Frontiers in Immunology, 2021)
Nowadays, in the study of rheumatoid arthritis (RA), more and more interest is directed towards an earlier effective therapeutic intervention and the determination of companion markers for predicting response to therapy with the goal to prevent progressive joint damage, deformities, and functional disability. With the present work, we aimed at quantifying in a cohort of early RA (ERA) patients naïve to DMARD therapy, proteins whose increase was previously found associated with RA: serum amyloid A (A-SAA) and alarmins. Five A-SAA variants (SAA1α, SAA1β, SAA1γ, SAA2α, and SAA2β) but also S100A8 and S100A9 proteins were simultaneously quantified in plasma applying a method based on single targeted bottom-up proteomics LC-MS/MS. First, we compared their expression between ERA (n = 100) and healthy subjects (n = 100), then we focused on their trend by monitoring ERA patients naïve to DMARD treatment, 1 year after starting therapy. Only SAA1α and SAA2α levels were increased in ERA patients, and SAA2α appears to mostly mediate the pathological role of A-SAA. Levels of these variants, together with SAA1β, only decreased under biologic DMARD treatment but not under methotrexate monotherapy. This study highlights the importance to better understand the modulation of expression of these variants in ERA in order to subsequently better characterize their biological function. On the other hand, alarmin expression increased in ERA compared to controls but remained elevated after 12 months of methotrexate or biologic treatment. The work overcomes the concept of considering these proteins as biomarkers for diagnosis, demonstrating that SAA1α, SAA1β, and SAA2α variants but also S100A8 and S100A9 do not respond to all early treatment in ERA and should be rather considered as companion markers useful to improve the follow-up of treatment response and remission state. Moreover, it suggests that earlier use of biologics in addition to methotrexate may be worth considering.